Gastric volvulus following diagnostic upper gastrointestinal endoscopy: a rare complication. (10th February 2014) - Karthikeyan, Vilvapathy Senguttuvan; Sistla, Sarath Chandra; Ram, Duvuru; Rajkumar, Nagarajan
Abstract : Esophagogastroduodenoscopy (EGD) is a commonly used, safe diagnostic modality for evaluation of epigastric pain and rarely its major complications include perforation, haemorrhage, dysrhythmias and death. Gastric volvulus has been reported to complicate percutaneous endoscopic gastrostomy but its occurrence after diagnostic EGD has not yet been reported in literature. The successful management relies on prompt diagnosis and gastric untwisting, decompression and gastropexy or gastrectomy in full thickness necrosis of the stomach wall. A 38-year-old woman presented with epigastric pain and EGD showed pangastritis. Immediately after EGD she developed increased severity of pain, vomiting and abdominal distension. Emergency laparotomy carried out for peritoneal signs revealed eventration of left hemidiaphragm with the stomach twisted anticlockwise in the longitudinal axis. After gastric decompression and untwisting of volvulus, anterior gastropexy and gastrostomy was carried out. Hence, we report this rare complication of diagnostic endoscopy and review the existing literature on the management.